Tratamento adjuvante da alodinia mecânica em pacientes com trauma raquimedular: um estudo clínico prospectivo de intervenção - Aline Duprat Ranos (2018)
Allodynia is a type of pain caused by an innocuous stimulus. Loss of specificity leads to changes from tactil and thermal perceptions into painful sensation (mechanical and thermal allodynia respectivly). Mechanical allodynia (AM) in people with spinal cord injury may have an early onset (imediatly after trauma). Monitoring MA, in order to prevent or minimize its progress as early as possible, is higlhly recommended after trauma in order to prevent below level neuropathic pain (NP) type